A KINETIC STUDY OF PYROLYSIS OF BAGASSE USING THERMOGRAVIMETRIC ANALYSIS - Rachmawanti, Octaviana; Subagyono, R.R. Dirgarini; Allo, Veliyana Londong (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2023)
A kinetic study of pyrolysis of bagasse using thermogravimetric analysis using the model-free methods, including the Kissinger-Akahira-Sunose (KAS) method and the Friedman method, has been carried out. The purpose of this study was to determine the pyrolysis decomposition process of bagasse and to determine the activation energy value of pyrolysis of bagasse. In this study, pyrolysis was carried out at various heating rates of 10, 15, 20, and 25 °C/minute using a Thermogravimetric Analyzer (TGA). The active pyrolysis temperature range of bagasse was + 104-431°C with a mass reduction of 56-64% where the decomposition process of cellulose, hemicellulose, and lignin in the biomass sample occurred. The activation energy obtained based on the KAS was 136.39 + 23.19 kJ/mol, wheres the activation energy obtained based on the Friedman method was 156.19 + 35.28 kJ/mol. Keywords: Bagasse, Pyrolysis, Thermogravimetry, Model-free, Activation Energy